‘Same Old Stories’: Sexist and Anti-Feminist Discourses in Greek Chick-Lit - Liotzis, Vangelis (Cultural Arts Research and Development, 2026)
This article examines the reproduction of sexist and anti-feminist discourses in contemporary Greek chick-lit through a critical discourse analysis of ten novels by Chrysiida Dimoulidou and Lena Manta. Situating the genre within post-feminist and neoliberal cultural contexts, the study interrogates how linguistic, discursive and narrative strategies construct and normalize restrictive conceptions of femininity and masculinities in popular romance fiction. Drawing on a classical Fairclough-informed framework, the analysis foregrounds recurring patterns—linguistic violence and abusive epithets, slut-shaming and body-shaming, portrayals of female hysteria and emotionality, hetero-determination via sexual relations, and the sacralization of motherhood—that function to depoliticize women’s agency and to naturalize gender hierarchies. Although fleeting emancipatory moments and individual claims to autonomy appear, they are fragmented and subordinated to conventional romantic resolutions (marriage, pairing, or withdrawal), which ultimately reinscribe the genre’s ideological closure. The paper argues that Greek chick-lit, while commercially successful and culturally resonant, frequently legitimizes ‘patriarchal common-sense’ through everyday language and plot conventions, thereby complicating assumptions of the genre as inherently empowering. By mapping thematic categories and providing close textual readings, the study contributes to feminist literary scholarship and calls for more sustained critical engagement with popular women’s fiction as a site where ideological meanings about gender are produced, reproduced and consumed.